Transport Properties of Bi2Te3 and Proximity Effect with Aluminum Superconductors - Ekström, Maria (My University, 2020)
Topological insulators are materials with an insulating bulk and a gap-less metallic surface. On the surface the energy dispersion is linear and described by an odd number of Dirac cones. The interest for these materials was renewed recently when room temperature topological insulators among the bismuth compounds was discovered. Intensive research in the last years is focusing on observing the signatures of the topological surface. However, it is di cult to isolate from the bulk and the e ects observed can have alternative interpretations. So far the surface states have not been totally distinguished from the bulk. Therefore topological insulators need further characterization and this thesis is a part of that research. The two main focuses were to characterize the transport properties of molecular beam epitaxy grown Bi2Te3 thin lms and Bi2Se3 single crystal with Hall e ect and proximity e ect. The Hall measurements of Bi2Te3 were used as feedback to the growers in collaboration to achieve better quality thin lms. The Bi2Te3 showed negative charge carriers and the volume carrier concentration was improved from 1x1021 cm3 to 4.4x1018 cm8. The mobility was improved from 150 cm2/Vs to 5500 cm2/Vs. For Bi2Se3 samples the typical values were 1.3 x 1019 cm3 and 5100 cm2/Vs, which was comparable with the best Bi2Te3 lms. The properties of the topological insulators Bi2Te3 and Bi2Se3 were also investigated using proximity induced superconductivity in Josephson junctions and superconducting quantum interference devices with aluminum contacts at temperatures down to 20mK. The Josephson coupling was con rmed by the response in microwave radiation and magnetic eld. The height of the observed steps corresponded well to integer Shapiro steps. The response of the devices in magnetic eld showed expected Fraunhofer patterns, where the e ective areas for both the Josephson junctions and the superconducting quantum interference devices was in good agreement with the design. In addition the temperature dependence of the junctions was examined and evaluated in the clean and dirty regimes. The critical current scaled with the temperature, according to simulations of the resistively shunted junction model. To further characterize the Bi2Te3 thin lm topography and spectroscopy was measured, describing the roughness of the lm and indicating a Dirac cone around 200mV.